Global child and adolescent mental health perspectives: bringing change locally, while thinking globally - Sowmyashree Mayur Kaku; Jordan Sibeoni; Salah Basheer; Jane Pei-Chen Chang; Dulangi Maneksha Amerasinghe Dahanayake; Matias Irarrazaval; Jamie M Lachman; Boladale Moyosore Mapayi; Anilena Mejia; Massimiliano Orri; Tze Jui-Goh; Md Saleh Uddin; et al. (BMC, 2022)
Abstract Child and adolescent mental health (CAMH) are a global priority. Different countries across the globe face unique challenges in CAMH services that are specific to them. However, there are multiple issues that are also similar across countries. These issues have been presented in this commentary from the lens of early career CAMH professionals who are alumni of the Donald J Cohen Fellowship program of the IACAPAP. We also present recommendations that can be implemented locally, namely, how promoting mental health and development of children and adolescents can result in better awareness and interventions, the need to improve quality of care and access to care, use of technology to advance research and practices in CAMH, and how investing in research can secure and support CAMH professionals and benefit children and adolescents across the globe. As we continue to navigate significant uncertainty due to dynamic circumstances globally, bolstering collaborations by "bringing change locally, while thinking globally" are invaluable to advancing global CAMH research, clinical service provision, and advancement of the field.